Ketakterjemahan dalam Terjemahan Puisi Jerman-Indonesia: Reproduksi Pesan dan Strategi Penerjemahan - Irsyad Kamal Hafirdin; Putrasulung Baginda; Hafdarani Hafdarani (Jurnal Bahasa dan Sastra, 2026)
This study examines untranslatability and message reproduction in the translation of German poetry into Indonesian. The research aims to identify forms of untranslatability, analyze the reproduction of messages in terms of accuracy, acceptability, and readability, and reveal the factors causing untranslatability in poetic translation. This study employed a descriptive qualitative method using purposive sampling. The data consisted of words, phrases, clauses, and sentences taken from the poetry collection Das durch Probleme lebendige Leben by Dani Hendra. The data were analyzed using Molina and Albir’s translation techniques, Catford’s theory of untranslatability, Venuti’s translation ideology, and Nababan’s translation quality assessment model. The findings indicate that modulation was the most frequently identified translation technique, followed by literal/calque, adaptation, discursive creation, and several other techniques. Linguistic untranslatability appeared more frequently than cultural untranslatability, particularly at the lexical and syntactic levels. The translator tended to prioritize acceptability and readability through domestication strategies, although several cases of foreignization were maintained to preserve cultural elements of the source text. The study concludes that message reproduction in poetry translation is conditional because aesthetic and communicative considerations often require compromises in propositional accuracy.